PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS BINA MARGA DAN BINA KONTRUKSI PROVINSI SUMATERA UTARA UPTJJ KABANJAHE - Maria Kristina Situmorang (JURNAL REGIONOMIC, 2021)
This study aims to determine and analyze the effect of motivation on employeeperformance at the Office of Highways and Construction of North Sumatra ProvinceUPTJJ Kabanjahe. In this study, the population was employees at the Office of Highwaysand Construction Services of North Sumatra Province UPTJJ Kabanjahe, totaling 38people and the entire population was sampled in this study as many as 38 people. Theresults of the validity test show that all statement items are valid becauser_(count )>r_table and all items are declared valid. The results of the study using the ttestshowed the value of t _(count )2,919 with a significant value of 0.006, while t_tablewas 1.668 so that t_(count)>t_table (2,919 > 1.668) then partially motivation affectedemployee performance. Significant research shows the number > 0.05 then H_o isrejected and H_a is accepted, meaning that motivation has a positive effect on employeeperformance. The results of the study using the Coefficient of Determination (R2) of43.7% which shows that the motivation variable affects employee performance.